CHANGES IN THE DAILY ROUTINE AND LIFE PERCEPTIONS OF OLDER ADULTS DUE TO THE CORONAVIRUS DISEASE 2019 (COVID-19) PANDEMIC - Rodrigo Garcia Fiorillo; Daniel Vicentini de Oliveira; Ágatha Graça; Higor Santos Fonseca; Flávio Ricardo Guilherme; Lenamar Fiorese; José Roberto Andrade do Nascimento Júnior; Fábio Luiz Cheche Pina; Jerry Mayhew; Matheus Amarante do Nascimento (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: This study aimed to analyze changes in the daily routine and life perceptions of older adults due to the coronavirus disease 2019 pandemic. METHODS: This is a cross-sectional study conducted with 338 older adults (93 men and 238 women) residing in southern Brazil. An online questionnaire consisting of 20 questions was created using the Google Forms platform and was distributed to older adults (> 60 years of age) during the isolation period caused by the coronavirus disease pandemic. Data analysis was conducted through Student's-t and χ2 tests. RESULTS: Our results showed a significant association between social isolation and sex (p < 0.01), revealing that women experienced higher levels of social isolation than men. We observed that 82.21% of the older adults participating in this study reported changes in their social routines during the pandemic. CONCLUSIONS: During this period of extended social isolation, women reported more negative effects than men.